Solution of the Hudson-Parthasarathy equation by ordered products - Waldenfels, Wilhelm von (Stochastics, 2017)
The solution of the quantum stochastic differential equation of Hudson and Partasarathy with constant coefficients can easily be formulated with the help of the normal ordered product. Introducing time ordering we obtain a new representation of the solution. This new representation gives an easy access to the Evans-Hudson flow and the unitary condition of Hudson and Parthasarathy. We use the measure theoretical white noise calculus.
Published online: 12 Jul 2016
Gesehen am 25.06.2018